A survey of microorganism and its biological effects in the straw covered field - Delgermaa, B; Sunjidmaa, O (Mongolian Journal of Agricultural Sciences, 2015)
This study compared and determined the quantities, types and biological activities of microorganisms in the soil covered and uncovered with straw. By creating straw mulch on the soil, the number of /nitrogen fixation/ useful bacteria has increased 1.3-2.2 times more than in the uncovered field. Also the cellular depleting bacteria around 0.7 million pieces, and the number of fungal pathogen 0.17 million pieces more than in the uncovered version. The soil biological activity has decreased 0.0037-0.0009 kg. hour/ha at the beginning of planting and at the end of harvesting. It depends on the number of bacteria. Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 86-90